1998
DOI: 10.1302/0301-620x.80b5.8830
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the disc space after fractures of the thoracolumbar spine

Abstract: We have studied the intervertebral discs adjacent to fractured vertebral bodies using MRI in 63 patients at a minimum of 18 months after injury. There were 75 thoracolumbar fractures of which 26 were treated conservatively and 37 by posterior reduction and fusion with an AO internal fixator. We identified six different types of disc using criteria based on the morphology and the intensity of the MRI signal. The inter- and intraobserver variability of this system was good. Most of the discs showed predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 22 publications
2
87
0
7
Order By: Relevance
“…This structure, with high expansive capacity, may creep into the defects in the endplate and expand itself into the vertebral body. Clinical observations support the hypothesis that this may be an important mechanism for explanation of the changes observed in the disc space after a fracture [18]. Another mechanism may be a rapid disc degeneration initiated by an annular tear.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This structure, with high expansive capacity, may creep into the defects in the endplate and expand itself into the vertebral body. Clinical observations support the hypothesis that this may be an important mechanism for explanation of the changes observed in the disc space after a fracture [18]. Another mechanism may be a rapid disc degeneration initiated by an annular tear.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, even if there is no change in the biological integrity of the disc, the changed morphology of the disc space as a result of the fracture of the vertebral body may alter its properties of resisting compressive forces. In a retrospective MRI study, Oner et al showed that all these different mechanisms may lead to different types of post-traumatic disc space changes, with possible consequences for the long-term stability of the injured segment [18]. The question of whether these different mechanisms can be predicted from patterns of injury detected with MRI should be studied in a prospective fashion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI analysis of the disc signal have showed no significant signal intensity modification, and more particularly, no degeneration process. According to Oner [2], the disc changes are the consequences of adaptation to the morphological changes of the end plate with settling of the end-plate defect. Indirect reduction does not allow restoration of the mechanical properties of the end plate-disc interface.…”
mentioning
confidence: 99%